2015
DOI: 10.1016/j.pedneo.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Lung Ultrasound in the Diagnosis of Community-acquired Pneumonia in Children

Abstract: LUS is a sensitive diagnostic tool with which to identify pneumonia in children. It is also useful in following up the progress of pneumonia. We suggest that LUS is a complementary tool to chest radiography in the diagnosis of pneumonia in children and that the follow up of pneumonia by LUS can reduce the exposure of children to ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 25 publications
6
69
0
Order By: Relevance
“…It should also be noted that LUS identified 5 additional cases in which no consolidation was visible on chest radiographs. Similar findings on higher performance of LUS as compared to chest radiographs in certain cases have been reported in the literature and among explanations is the reduced dimension of the lung consolidations, too small to be identified by radiography, and the location of the lesions behind the heart or mediastinum [16,24]. Head-to-head comparisons of chest radiological and LUS findings, with chest computed tomography (CT) as a reference standard, are available only in adults and showed a higher accuracy of LUS in the detection of lung changes [25].…”
Section: Se % (95%ci) Sp % (95%ci) Ppv% (95%ci) Npv % (95%ci) Plr (95supporting
confidence: 82%
See 2 more Smart Citations
“…It should also be noted that LUS identified 5 additional cases in which no consolidation was visible on chest radiographs. Similar findings on higher performance of LUS as compared to chest radiographs in certain cases have been reported in the literature and among explanations is the reduced dimension of the lung consolidations, too small to be identified by radiography, and the location of the lesions behind the heart or mediastinum [16,24]. Head-to-head comparisons of chest radiological and LUS findings, with chest computed tomography (CT) as a reference standard, are available only in adults and showed a higher accuracy of LUS in the detection of lung changes [25].…”
Section: Se % (95%ci) Sp % (95%ci) Ppv% (95%ci) Npv % (95%ci) Plr (95supporting
confidence: 82%
“…In our study, compared to chest radiographs, LUS correctly identified 57 of the children with radiological pneumonia, while in 15 cases no condensation was visible by LUS. Among the reasons for LUS not detecting the lung modifications are the location of lesions in areas not easily reached by ultrasound beam or lesions of small dimensions that do not extend to pleura [24]. In our study the performance of LUS when using chest radiographs as a reference standard was 79.2% (sensitivity) and 44.4% (specificity), respectively.…”
Section: Se % (95%ci) Sp % (95%ci) Ppv% (95%ci) Npv % (95%ci) Plr (95mentioning
confidence: 52%
See 1 more Smart Citation
“…Our multivariate analysis produced the novel finding that a fluid bronchogram is a risk factor for a poor outcome. A fluid bronchogram is an anechoic tubular structure along the bronchial tree and is an established feature of pneumonia that is found in approximately 20% of patients with pneumonia [10,21]. It develops in the early phase of the disease as a result of bronchial secretions or edema [9,21].…”
Section: Discussionmentioning
confidence: 99%
“…For each case, six sectors of each lung (upper and lower anterior, lateral, and posterior) were examined. The following TUS features of pneumonia were recorded: (1) air bronchogram (Fig 2), the presence of hyperechoic spots caused by small bubbles of trapped air; (2) fluid bronchogram (Fig 3), the presence of mucus-filled tubular structures with echogenic walls, with no color-Doppler signal; (3) increased B-lines (Fig 4), the presence of more than three B-lines per scan; (4) a vascular pattern (Fig 5), the presence of enhanced color-Doppler signal, tree-like vascularity in the consolidation; and (5) pleural effusion (6) [9,10,17,18]. The focal depth of sonomorphology for detecting pneumonia in children is 5 to10 cm.…”
Section: Performance Of Tusmentioning
confidence: 99%